2001
DOI: 10.1557/proc-671-m6.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of pH On Chemical-Mechanical Polishing Of Copper And Tantalum

Abstract: ABSTRACTpH has a strong effect on the polish rates of copper (Cu) and tantalum (Ta) [1]. In this paper, removal rates of Cu and Ta using aqueous slurries containing alumina and silica abrasives in H2O2-glycine solution are studied at varying pH values. It is observed that variation in the Cu and Ta removal rates is a direct result of the change in surface characteristics of the films. Surface characteristics such as presence/absence of a passivating layer and hardness of such layer vary with pH and hence resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…To optimize the CMP process, various chemicals, abrasives, polishing pads, etc. have been investigated [4][5][6][7][8][9][10][11][12]. However, due to a large number of parameters that can influence the CMP process, the optimization of CMP by experimental means has been difficult.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the CMP process, various chemicals, abrasives, polishing pads, etc. have been investigated [4][5][6][7][8][9][10][11][12]. However, due to a large number of parameters that can influence the CMP process, the optimization of CMP by experimental means has been difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The variation in MRR with pH is due primarily to variations in electrostatic interactions between the particles and the Ta surface. Jindal et al [8] investigated the effect of pH on CMP of Cu and Ta and found that MRR of copper decreased monotonically from pH 2 to pH 12, while a less protective Ta surface layer in alkaline region resulted in a high MRR of Ta. It was suggested that a favorable Cu/Ta polishing rate selectivity can be obtained by regulating slurry pH.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, slurry pH and the concentration levels of H 2 O 2 have been found to result in the formation of a hard passivation layer of CuO or Cu 2 O on the surface of the Cu [4,5]. In general, and in accordance with the Cu Pourbaix diagram [6], a number of studies have shown that surface chemistry in the basic region combined with a given peroxide concentration, can lead to the formation of CuO.…”
Section: Introductionmentioning
confidence: 80%
“…In Cu CMP, abrasive particles such as alumina or colloidal silica are suspended in the slurry and aid in mechanical removal while slurry pH and hydrogen peroxide (H 2 O 2 ) provide the chemical reactions needed to facilitate the removal of Cu. Although extensive research has been conducted investigating the effects of slurry pH and H 2 O 2 during CMP [3][4][5], limited work has been done exploring the interaction effects between the two variables when dealing with thick Cu layers. The effect of slurry pH and complexing agents such as EDTA, citric acid and glycine on Cu removal rates has been well documented [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation